A National Palliative Care Strategy for Canada - Morrison, R. Sean (J Palliat Med, 2017)
Objective: To identify barrier to achieving universal access to high quality palliative care in Canada, review published national strategies and frameworks to promote palliative care, examine key aspects that have been linked to successful outcomes, and make recommendations for Canada. Background: In 2014, the World Health Organization called on members to develop and implement policies to ensure palliative care is integrated into national health services. Methods: Rapid review supplemented by the author's personal files, outreach to colleagues within the international palliative care community, review of European Association for Palliative Care publications, and a subsequent search of the table of contents of the major palliative care journals. Results: Frameworks were found for 10 countries ranging from detailed and comprehensive multi-year strategies to more general approaches including laws guaranteeing access to palliative care services for “dying” patients or recommendations for the development of clinical infrastructure. Few formal evaluations were found minimal comparative data exist regarding the quality of care, access to palliative care services, timing of access in the disease trajectory, and patient and family satisfaction with care. Factors that appear to be associated with success include: 1) input and early involvement of senior policy makers; 2) comprehensive strategies that address major barriers to universal access and that involve the key constituents; 3) a focus on enhancing the evidence base and developing a national system of quality reporting; and 4) substantial and sustained government investment. Discussion: Comprehensive national strategies appear to improve access to high quality palliative care for persons with serious illness and their families. Such strategies require sustained government funding and address barriers related to infrastructure, professional and public education, workforce shortages, and an inadequate evidence base.